2012
DOI: 10.1016/j.jval.2012.08.2160
|View full text |Cite
|
Sign up to set email alerts
|

PCN120 Quality of Life Among German Patients With Metastatic Castration-Resistant Prostate Cancer

Abstract: Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30), a PRO instrument specifically designed to measure HRQoL of cancer patients. HRQoL was measured at screening, months 1, 3, 7, and at re-puncture. Meaningful deterioration was defined as a decrease in HRQoL scores of at least 5 points. Time to first meaningful deterioration was compared between catumaxomab (Nϭ160) and control (Nϭ85) groups using survival analysis techniques such as log-rank test and Cox models. RESULTS: Deterioration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Very little other information exists regarding the HRQOL of men with metastatic CRPC in the period of time before chemotherapy becomes clinically indicated (group 1) or is received (group 2). The EQ-5D utility values elicited in the present study are similar to EQ-5D utility values elicited from a German sample (0.81 before chemotherapy, 0.64 undergoing chemotherapy, 0.66 previously been treated with chemotherapy) [19]. Mean EQ-5D utility values from mixed country/treatment stage metastatic CRPC samples range from 0.59 (French, German, Italian, Spanish, and UK patients with/at high risk of developing bone metastases [13], mixed chemotherapy naive, current and prior chemotherapy New Zealand patients [15]) to 0.76 (mixed chemotherapy naive, current and prior chemotherapy German patients [15]).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Very little other information exists regarding the HRQOL of men with metastatic CRPC in the period of time before chemotherapy becomes clinically indicated (group 1) or is received (group 2). The EQ-5D utility values elicited in the present study are similar to EQ-5D utility values elicited from a German sample (0.81 before chemotherapy, 0.64 undergoing chemotherapy, 0.66 previously been treated with chemotherapy) [19]. Mean EQ-5D utility values from mixed country/treatment stage metastatic CRPC samples range from 0.59 (French, German, Italian, Spanish, and UK patients with/at high risk of developing bone metastases [13], mixed chemotherapy naive, current and prior chemotherapy New Zealand patients [15]) to 0.76 (mixed chemotherapy naive, current and prior chemotherapy German patients [15]).…”
Section: Discussionsupporting
confidence: 71%
“…Several studies are published only as non-peer reviewed conference abstracts, and information is lacking for patients with metastatic CRPC who have progressive disease in the period before chemotherapy becomes clinically indicated. Utility values for this subgroup have been reported in a German study [19], but this has not previously been investigated in a UK sample.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Therefore, the effect of PSA progression on HRQL was probably underestimated since the literature shows that HRQL decreases further with time. 2,5 Later in treatment utility can improve with successful therapy. Utilities as high as 0.81 were seen in patients still receiving cabazitaxel at 10 cycles vs 0.698 at baseline while utility during end of life care in the average patient is much lower at 0.5 to 0.6.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19][20] A further study involving patients with CRPC reported that HRQoL was worse for patients with bone metastases than for patients without bone metastases (0.59 vs 0.77, respectively). 21 • An observational study investigating HRQoL according to stage of disease reported that utility values decreased from 0.87-0.90 for patients with localized disease to 0.74 for those with metastases and 0.59 for those receiving palliative care.…”
Section: Prostate Cancermentioning
confidence: 99%